Management of extremity and pelvic fractures in earthquake: our observations and recommendations - Bugra Kundakci; Akif Mirioglu; Bugra Eraslan; Hakki Can Olke; Mustafa Tekin; Melih Bagir; Yusuf Kemal Arslan (BMC Musculoskeletal Disorders)
Abstract Background Earthquakes frequently cause injuries to the musculoskeletal system. Studies conducted after earthquakes often report on injured limbs, fractures, and surgeries. This study aimed to enhance preparedness for future earthquakes by acquiring knowledge about the prevalence of fractures and the relationship between fracture types and injury mechanisms. Methods A retrospective analysis was conducted on medical records of patients with fractures admitted to our hospital following the 2023 Kahramanmaraş Earthquake. Patients with fractures resulting from traffic accidents or other causes unrelated to earthquakes were excluded. The recorded data included age, gender, fracture site, fracture type, mechanism of injury, date, duration of surgery, and peak creatine kinase (CK) level. The injury mechanisms were classified into four main categories: injured by falling objects, falling while running, falling from height, and being trapped under rubble. The study investigated the relationship between fractures and other factors. Results The study included 185 patients with a mean age of 39.62 ± 20.83 years. The most frequent mechanism of injury was being trapped under rubble. In total, there were 214 fractures, with pelvic fractures being the most common (21.50% of all fractures). Tibia fractures were the most common fractures in the lower extremities (15.89%). Women had a significantly higher occurrence of pelvic fractures (33.3%) compared to men (14.5%) (p = 0.003). The frequency of pelvic fractures significantly increased as age decreased (p = 0.007). Patients with pelvic fractures had a significantly greater peak CK concentration (p = 0.006). Open fractures were more common in the first few days, and Kirschner wires were the first treatment applied at a mean of 74 h and external fixators at a mean of 94.3 h. Conclusion Injuries from falling objects from roofs and jumping from heights are important in earthquakes. In addition to lower extremity fractures, pelvic fractures are common in earthquake disasters. Most pelvic fractures are simple lateral compression fractures and it is important to follow the patients for crush syndrome in the first days instead of focusing on definitive fracture treatment. Open fractures should be prioritized for fracture surgery within the first few days. External fixators and Kirschner wires are recommended. Closed fractures should be treated conservatively and definitive surgical procedures should be postponed to the following weeks.